A Fuzzy-Based Spatial Condition Detection System Using Square Area Mapping to Support The Mobility of Individuals with Visual Impairments - Tata Supriyadi; Ridwan Solihin; Endang Habinuddin; Sudrajat Sudrajat; TB Utomo; Budi Setiadi; Ramdhan Nugraha (Sultan Publisher, 2025)
This research developed, designed, and implemented a cane prototype with the ability to identify spatial conditions, which can help the mobility of blind people in the form of decision information on choosing a path that is free from obstacles. The electronic space sensing system uses ultrasonic-type non-contact/non-visual sensors. Ultrasonic sensors are installed at three points: left, front, and right (L, F, R) of the stick. When the stick swings left-right or vice versa, each sensor will produce an array of distance data and then average it. The average distance of each point is calculated by the Left Side Square Area (LSSA) and Right Side Square Area (RSSA). The LSSA and RSSA values ​​are used as fuzzy input, a fuzzy inference process is carried out using a rule base, and defuzzification is used for decision output on the microcontroller. The system translates the decision results into sound (beep) and vibration information for the user. The results of the second experiment with blind people in two different scenarios show that the system can be an effective support during mobility in the hall and is a feasible prototype for training blind people with new O&M techniques towards the use of travel aids.